Management of Five Hundred Patients With Gut Failure at a Single Center: Surgical Innovation Versus Transplantation With a Novel Predictive Model. Issue 4 (October 2019) - Abu-Elmagd, Kareem M.; Armanyous, Sherif R.; Fujiki, Masato; Parekh, Neha R.; Osman, Mohammed; Scalish, Marissa; Newhouse, Elizabeth; Fouda, Yasser; Lennon, Elizabeth; Shatnawei, Abdullah; Kirby, Donald; Steiger, Ezra; et al.
Abstract : Objective(s): To define the evolving role of integrative surgical management including transplantation for patients gut failure (GF). Methods: A total of 500 patients with total parenteral nutrition-dependent catastrophic and chronic GF were referred for surgical intervention particularly transplantation and comprised the study population. With a mean age of 45 ± 17 years, 477 (95%) were adults and 23 (5%) were children. Management strategy was guided by clinical status, splanchnic organ functions, anatomy of residual gut, and cause of GF. Surgery was performed in 462 (92%) patients and 38 (8%) continued medical treatment. Definitive autologous gut reconstruction (AGR) was achievable in 378 (82%), primary transplant in 42 (9%), and AGR followed by transplant in 42 (9%). The 84 transplant recipients received 94 allografts; 67 (71%) liver-free and 27 (29%) liver-contained. The 420 AGR patients received a total of 790 reconstructive and remodeling procedures including primary reconstruction, interposition alimentary-conduits, intestinal/colonic lengthening, and reductive/decompressive surgery. Glucagon-like peptide-2 was used in 17 patients. Results: Overall patient survival was 86% at 1-year and 68% at 5-years with restored nutritional autonomy (RNA) in 63% and 78%, respectively. Surgery achieved a 5-year survival of 70% with 82% RNA. AGR achieved better long-term survival and transplantation better ( P = 0.03) re-established nutritional autonomy. Both AGR and transplant were cost effective and quality of life better improved after AGR. A model to predict RNA after AGR was developed computing anatomy of reconstructed gut, total parenteral nutrition requirements, cause of GF, and serum bilirubin. Conclusions: Surgical integration is an effective management strategy for GF. Further progress is foreseen with the herein-described novel techniques and established RNA predictive model. Abstract : Supplemental Digital Content is available in the text